Soft tissue development around pontic site: A case series - Sarita Joshi Narayan; Pranav Kumar Singh; Achut R Devarhubli; R Keerthi (Wolters Kluwer Medknow Publications, 2016)
An ideal emergence profile is vital for maintaining gingival health and developing esthetics. The ovate pontic which mimics a natural tooth gives the most appropriate emergence profile. For a successful ovate pontic restoration, an alveolar ridge of sufficient height and width is necessary to enhance the deficient ridge and to achieve an esthetic emergence profile. Interpositional graft was carried out along with ovate pontic to achieve an ideal esthetic restoration. After three months of the postoperative period, there was an increased horizontal dimension in the deficient ridge and an esthetic emergence profile. Interpositional graft technique is a simpler and predictable technique for pontic site development in moderate cases of bucco-lingual ridge deficiency.